Ag nanoparticles anchored NiO/GO composites for enhanced capacitive performance. Issue 11 (15th August 2016) - Zhou, E.; Wang, Chenggang; Deng, Xiaolong; Xu, Xijin
Abstract: Hierarchical nickel oxide/graphene oxide (NiO/GO) and nickel oxide/graphene oxide/silver (NiO/GO/Ag) heterostructures were sucessfully fabricated as high-performance supercapacitors electrode materials by using a hydrothermal process and a photoreduction process. The experimental results showed that the NiO/GO/Ag heterostructure electrodes showed better electrochemical performance than those of NiO/GO and bare NiO nanosheets. The NiO/GO/Ag electrode exhibited a higher specific capacitance of 229 F g −1 at a current density of 1 A g −1, higher than that of 161 F g −1 for NiO/GO composites. Furthermore, NiO/GO/Ag electrode also showed good rate capability (still 200 F g −1 at 6 A g −1 ) and cycling stability (24% loss after 2000 repetitive cycles at a scan rate of 20 mV s −1 ). The enhanced capacitive performance of the NiO/GO/Ag composites was mainly attributed to the introduction of Ag nanoparticles, which increased the electrical conductivities of the composites, and promoted the electron transfer between the active components. This study suggested that NiO/GO/Ag composites were a promising class of electrode materials for high performance energy storage applications.